Luminescent ecstasy tablets. Authentication tool or cunning marketing tactic?. (April 2015) - Cox, M.; Cook, M.
Graphical abstract: Highlights: We report the detection of two types of phosphorescent ecstasy tablets. We determine the identity of the phosphor's present in both types of phosphorescent ecstasy tablets. The presence of one of these phosphor's is used to link an ecstasy tablet from an 'unrelated' case. We report the detection of two types of fluorescent ecstasy tablets. The source of the fluorescence from one of the types of fluorescent ecstasy tablets is determined. Abstract: Forensic Science SA (FSSA) in combination with South Australia Police (SAPOL) has detected luminescent ecstasy tablets. This paper examines the emergence of luminescent ecstasy tablets and their potential role as an extra level of authentication for the user and/or as a marketing tactic aligned with their use at glow parties.